Feasibility and safety of passive cooling in a cohort of asphyxiated newborn infants (Swiss Medical Weekly, 2013)
OBJECTIVE: Therapeutic hypothermia has become a standard neuroprotective treatment in term newborn infants following perinatal asphyxia. Active cooling with whole body surface or head cooling is complex, expensive and often associated with initial hypothermic overshoot. We speculated that passive cooling might suffice to induce and maintain hypothermia. METHODS: We analysed 18 asphyxiated term newborns treated with hypothermia in three tertiary neonatal and paediatric intensive care units. Target temperatures of 33.5 °C or 33.0 °C were induced and maintained by turning off the heating system of the open neonatal care unit and by using analgesics and sedatives. We compared our results with matching published data from the hypothermia trial of the National Institute of Child Health and Human Development (NICHD) neonatal research network. RESULTS: Four infants required no active cooling at all during the whole cooling period. The other 14 infants had passive cooling during 85% of the total cooling time, and active cooling with ice packs in 15% of the total cooling time. Overshoot was smaller in the present study than in the NICHD study. CONCLUSION: Passive cooling for asphyxiated newborns appears to be feasible for induction and maintenance of hypothermia with a lower risk of overshoot.